Personal sales success factors in a wealthy market environment - Stros, Michael; ?íha, David; ?íhová, Elena; Lim, Lynn L.K. (Journal of Eastern European and Central Asian Research (JEECAR), 2019)
This study aimed to determine the success factors in personal sales in a wealthy market environment. For this purpose, a quasi-experimental design was formulated and the Swiss automotive market was selected. This market has some peculiarities in comparison to other markets, such as generally wealthy customers who demand fuel-efficient cars with significant horse power in the higher price range. Videos of personal sales conversations were produced and shown to the study participants for evaluation. The sales took place in the automotive sector, but the results can be transferred to other sectors. The theoretical concept of personal sales is introduced, sales theories, techniques and strategies are discussed. The different types of communication are introduced and explained. As a result, a factor analysis is conducted in order to interpret the results. The paper provides then conclusions by discussing and construing the results. Theoretical and managerial contributions and possible limitations are derived.